Peran Pekerja Sosial dalam Membantu Orang dengan HIV/AIDS (ODHA) Menghadapi Stigma Masyarakat - Mohammad Ilham Nadlifuddin (Politeknik Kesejahteraan Sosial Bandung, 2024)
People living with HIV/AIDS (PLWHA) have become a national discourse as a problem that needs to be addressed both in infected individuals and in social behavior towards PLWHA. Unfortunately, even though massive treatment has been carried out, the negative stigma of the surrounding community is still attached to PLWHA. This research will further explore how social work is carried out in the social restoration of community stigma towards PLWHA by the DIY Social Service. Research data was collected through two data search techniques, namely non-participant observation and in-depth interviews. The results of the research show that the DIY Social Service has carried out a number of activities in the form of preventive actions to restore the social stigma of society towards PLWHA in the Yogyakarta Province. Some of these actions include leaflets on social media, radio broadcasts, social propaganda through talk shows and wayang cangkruk, as well as supervision of Social Welfare Institutions (LKS) operating in DIY Province. However, researchers managed to find weaknesses in the program, indicated by the strong negative stigma towards PLWHA in society. The researcher further suggested that social restoration needs to be carried out in a more inclusive and targeted manner